Resistências e protagonismos das mulheres camponesas no sertão do Ceará - Batista, Maria Aline da Silva (2023)
The thesis seeks to reveal the link between peasant production of agroecological foods, gender equity, and food sovereignty. In this sense, the general objective is to analyze the strategies of resistance and political protagonism used by peasant women, based on Agroecology, in the hinterland of Ceará. For this, the following specific objectives were outlined: to discuss the intersectionality between the gender issue and the agrarian issue; to investigate women's struggle for political participation and the insertion of peasant women asa target audience for public policies; and, identify the practices of peasant women in agroecological production and marketing in Ceará. As a time frame, the period from 2000 to 2020 was delimited, as this is a historic moment of political ruptures, advances, and setbacks for peasants. The spatial focus is the state of Ceará, as it is representative of the problems of water scarcity, but which, however, has been the locus of experiences of resistance and alternatives for living with the drought. Furthermore, it is inserted in a region – the Northeast, historically subordinated, which has suffered and still suffers a process of double colonization – external and internal (ANDRADE, 2011; FURTADO, 2005; OLIVEIRA, 2008). The methodology for collecting data in the field took place in two ways: initially, due to health restrictions imposed by the Covid-19 pandemic in 2020, it followed the principles of Virtual Ethnography (KOZINETS, 2014), which brings together a set of procedures for ethnographic research on or through the internet, especially social media. Thus, the first contacts were virtual, through the google meet platform, or conversations recorded in audio via the Whatsapp application. Subsequently, with the easing of restrictive measures, we carried out fieldwork at agroecological fairs and in rural communities in the hinterland of Ceará. As a philosophical basis, we resorted to authors who discuss socio-spatial issues from the perspective of the regressive-progressive method, proposed by Henri Lefebvre (1978 apud MARTINS, 1996). In this line, the construction of the research will be supported by geographical (MARQUES, 2008; OLIVEIRA, 2007), sociological (MARTINS, 1983), and anthropological (HEREDIA, 1979; WOORTMANN, 1988) theories on the Agrarian Question, the Peasantry, the Territory, as well as on Agroecology (TOLEDO, 2016), the Female Gender (DAVIS, 2016; FEDERICI, 2017; SCOTT, 2019) and Food Sovereignty (CHONCHOL, 2005; ROSSET, 2006). In addition to the theoretical framework, a qualitative interpretation of the data was chosen, since this is a descriptive-analytical study. Based on readings and data collected in the field, it was identified that the agrarian issue in Brazil, as well as in Ceará, persists and is strongly related to the increase in inequalities between genders. The insertion of women, as a priority public, in agrarian policies in Brazil was the result of the political mobilization of peasant women, representing a step forward. However, the country's political instability reveals the fragility of Brazilian democracy and the need to strengthen links with other popular sectors. In Ceará, the agroecological fairs are distributed throughout the state and are promoted, mostly, by women who work at home, in agricultural production, and, often, in the life of a marketer. Among the resistance strategies used by peasant women in Ceará, the following can be pointed out: the conquest of financial autonomy; the collective and individual work in the maintenance of the productive units; the organization of production and commercialization of agroecological products, based on relationships such as kinship, neighborhood, and religiosity.